Sodium bicarbonate and sodium bentonite supplements for cattle fed corn or sorghum silages - Axe, D.; Bolsen, K.; Jacques, K.; Harmon, D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Supplementing forage sorghum silage rations with sodium bicarbonate (NaHCO3 ) improved performance of growing cattle over the control supplement. However, neither NaHCO 3 nor sodium bentonite supplementation to corn silage rations improved cattle performance.
Keywords: Beef; Sodium bicarbonate; Sodium bentonite; Corn silage; Sorghum silage